Dragonfly Diversity in Cibodas Botanical Garden in West Java - Susanti Murwitaningsih; Agus Pambudi Dharma; Maryanti Setyaningsih; Yati Nurlaeni (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
The dragonfly (Odonata) is a flying insect that plays an important role in the food chain and acts as a bioindicator of water health. This is due to its biological characteristics which include spending most of its life stages in the water and preying on smaller insects. This study is aimed to investigate the level of dragonfly diversity in Cibodas Botanical Garden, West Java. The method used in this research was direct observation using catch and release technique. The research was carried out from May to July 2018. A total of 1,510 individuals belonging to eight dragonfly species were found in the four sampling locations. These were divided into two Sub-Orders: 1) Anisoptera (Orthetrum pruinosum, Pantala flavences, Orthetrum sabina, Neurothemis fluctuans, Neurothemis terminata, and Orthetrum glaucum); and 2) Zygoptera (Ischnura senegalensis, dan Ceoliccia membranipes). The highest values of species diversity index (H') and evenness index (E) were found in Ciismun Waterfall (1,45 and 0,88, respectively). The dominance index (D) in the four sampling sites ranged between 0.25 - 0.32. The highest species richness index (R) was found in Sakura Garden (0,99).